Genuine Zoocentrism or Dogged Anthropocentrism? On the Personification of Animal Figures in the News - Gouabault, Emmanuel; Dubied, Annik; Burton-Jeangros, Claudine (Humanimalia, 2011)
Human-Animal relationships are changing and the media coverage of animal issues plays a major part in these transformations. The personification of animals is a socially-constructed process through which the status of a person is attributed to an animal. In this article, we analyze this process in the media, through successive analytical steps. Identifying the attributes of animal personification enables us to distinguish three increasingly complex levels of this process. In the most developed stage, the process of ‘starification’ is applied to the animal, such as in the 2007 case of the polar bear Knut, the abandoned cub of the Berlin Zoo. Using the ‘contrasted portrait’ approach, we then compare this story to an opposite animal figure, also making headline news in the media at the same time, namely the three pitbulls dogs who killed a child on his way to school in the eastern part of Switzerland. This analysis illustrates a number of current mutations in human-animal relationships and challenges the idea of ‘growing zoocentrism.’ Indeed, personified animals transformed in human figures rather than promoted as subjects of interest in themselves, suggest a permanence of anthropocentrism.